2020
DOI: 10.1242/bio.050435
|View full text |Cite|
|
Sign up to set email alerts
|

TRBP–Dicer interaction may enhance HIV-1 TAR RNA translation via TAR RNA processing, repressing host-cell apoptosis

Abstract: The transactivating response (TAR) RNA-binding protein (TRBP) has been identified as a double-stranded RNA (dsRNA)-binding protein, which associates with a stem-loop region known as the TAR element in human immunodeficiency virus-1 (HIV-1). However, TRBP is also known to be an enhancer of RNA silencing, interacting with Dicer, an enzyme that belongs to the RNase III family. Dicer cleaves long dsRNA into small dsRNA fragments called small interfering RNA or microRNA (miRNA) to mediate RNA silencing. During HIV-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…There is concern that the excision of miRNA or miRNAlike fragments could result in cleavage of the viral genome and hinder viral replication [99]. It has been suggested that the HIV encodes a transactivating response (TAR) motif that includes miRNA precursors that can be produced without cleavage of the viral genome [100,101]. However, the exact mechanism of this non-canonical pathway of miRNA production is still under investigation [100,101].…”
Section: Pro-viral Mirna Regulation Of Viral Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is concern that the excision of miRNA or miRNAlike fragments could result in cleavage of the viral genome and hinder viral replication [99]. It has been suggested that the HIV encodes a transactivating response (TAR) motif that includes miRNA precursors that can be produced without cleavage of the viral genome [100,101]. However, the exact mechanism of this non-canonical pathway of miRNA production is still under investigation [100,101].…”
Section: Pro-viral Mirna Regulation Of Viral Infectionmentioning
confidence: 99%
“…It has been suggested that the HIV encodes a transactivating response (TAR) motif that includes miRNA precursors that can be produced without cleavage of the viral genome [100,101]. However, the exact mechanism of this non-canonical pathway of miRNA production is still under investigation [100,101]. That said, v-miR-TAR has been detected in the sera of HIV-infected patients along with HIV-encoded v-miR-88 and v-miR-199 [102].…”
Section: Pro-viral Mirna Regulation Of Viral Infectionmentioning
confidence: 99%
“…HIV-1 also recruits host TAR RNA-binding protein (TRBP-known to be involved in RNA silencing) at TAR elements and resolve the secondary structure for translation initiation. This year, Komori et al (2020) showed that TRBP interacts with the DICER and mediates TAR miRNA degradation, reliving the hurdle. Apart from canonical translation initiation, eukaryotes and many viruses, including HIV-1, employ a capindependent translation mechanism.…”
Section: Cytoplasm: the Site Of Viral Protein Translation And Interacmentioning
confidence: 99%
“…The 5′-terminal TAR stem-loop structure of HIV RNAs impedes efficient translation of the viral RNAs ( 4 ) and TRBP binding to this element relieves this negative effect. Interestingly, Dicer was also recently proposed to be involved in this process ( 5 ). TRBP was additionally shown to promote HIV infection by directly or indirectly inhibiting PKR activation, which is triggered by the TAR RNA and leads to global translation inhibition ( 6 ).…”
Section: Introductionmentioning
confidence: 99%